Pengelolaan Aktivitas Media Sosial Instagram @cimahikota oleh Pemerintah Kota Cimahi - Fasya Al Rahmah; Hanny Hafiar; Heru Ryanto Budiana (Unitri Press, 2022)
The low engagement of social media accounts and the absence of real-time interaction with the closing of the Instagram comment column made the authors conduct a study entitled